2023
DOI: 10.1021/jacs.3c00801
|View full text |Cite
|
Sign up to set email alerts
|

Radical Caging Strategy for Cholinergic Optopharmacology

Abstract: Photo-caged methodologies have been indispensable for elucidating the functional mechanisms of pharmacologically active molecules at the cellular level. A photo-triggered removable unit enables control of the photo-induced expression of pharmacologically active molecular function, resulting in a rapid increase in the concentration of the bioactive compound near the target cell. However, caging the target bioactive compound generally requires specific heteroatom-based functional groups, limiting the types of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Inspired by UV-light induced β-scission observed in N -heterocyclic carbene boranes, blue-light (440 nm) induced β-scission of boracenes, and recent utility of electron-rich boryl radicals as nucleophiles in synthetic chemistry it was hypothesized that boron-functionalized variants of BODIPY fluorophores could provide a novel Type I photoinitiator platform for rapid and efficient free radical polymerization. Moreover, it was recently shown that boron-ethylated BODIPY could be used as a turn-on fluorescent sensor upon irradiation with a high intensity blue laser (488 nm, ≥28 W/cm 2 ), resulting in substitution of the ethyl functionality, although the mechanism was not reported .…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by UV-light induced β-scission observed in N -heterocyclic carbene boranes, blue-light (440 nm) induced β-scission of boracenes, and recent utility of electron-rich boryl radicals as nucleophiles in synthetic chemistry it was hypothesized that boron-functionalized variants of BODIPY fluorophores could provide a novel Type I photoinitiator platform for rapid and efficient free radical polymerization. Moreover, it was recently shown that boron-ethylated BODIPY could be used as a turn-on fluorescent sensor upon irradiation with a high intensity blue laser (488 nm, ≥28 W/cm 2 ), resulting in substitution of the ethyl functionality, although the mechanism was not reported .…”
Section: Introductionmentioning
confidence: 99%